A comparison of the skewness of stock return distributions at earnings and non-earnings announcement dates - McNichols, Maureen (Journal of Accounting and Economics, 1988)
This paper presents evidence that stock return prediction errors are less positively skewed in the time period surrounding accounting earnings report announcements than in a subsequent non- announcement period. Assuming that information available about firms in non-announcement periods depends on discretionary disclosure practices of firms and discretionary search for information by investors, the results suggest that earnings reports cause more extreme ‘bad news’ to be reflected in stock prices relative to discretionary sources of information.